2007
DOI: 10.1038/sj.npp.1301401
|View full text |Cite
|
Sign up to set email alerts
|

Arousal and Stress Effects on Consolidation and Reconsolidation of Recognition Memory

Abstract: This study examined the effects of the arousal level of the rat and exposure to a behavioral stressor on consolidation and reconsolidation of a nonaversive learning paradigm, the object recognition task. Learning was tested under two arousal conditions: no previous habituation to the experimental context (high novelty stress/arousal level) or extensive prior habituation (reduced novelty stress/arousal level). Results indicated that in the habituated rats, exposure to an out-of-context stressor (ie, elevated pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

12
103
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(116 citation statements)
references
References 70 publications
12
103
1
Order By: Relevance
“…In order to test the first possibility, we previously studied the immediate and prolonged effects of both cortisol and propranolol administration on declarative memory retrieval. We found that declarative memory can be impaired long-term when memories are reactivated during high levels of stress (Tollenaar et al 2008b) or after cortisol administration (Tollenaar et al 2008c), in line with animal research (Cai et al 2006;Maroun and Akirav 2007). In contrast, we did not find any immediate or long-term effects of propranolol on declarative memory after reactivation (Tollenaar et al 2008c), which is consistent with findings by de Quervain et al (2007).…”
supporting
confidence: 90%
See 1 more Smart Citation
“…In order to test the first possibility, we previously studied the immediate and prolonged effects of both cortisol and propranolol administration on declarative memory retrieval. We found that declarative memory can be impaired long-term when memories are reactivated during high levels of stress (Tollenaar et al 2008b) or after cortisol administration (Tollenaar et al 2008c), in line with animal research (Cai et al 2006;Maroun and Akirav 2007). In contrast, we did not find any immediate or long-term effects of propranolol on declarative memory after reactivation (Tollenaar et al 2008c), which is consistent with findings by de Quervain et al (2007).…”
supporting
confidence: 90%
“…If it would be possible to affect memory traces after they have been formed and retrieved, this could improve the treatment of stress-and memory-related disorders, like post traumatic stress disorder (PTSD) and phobias (de Quervain and Margraf 2008;Debiec and Ledoux 2006). Promising in this view is animal research that has shown that stress hormones like corticosterone (a glucocorticoid that resembles cortisol, but is naturally more abundantly present in rodents) and beta-adrenergic blocking agents like propranolol can affect long-term memory when administered during or after reactivation of the existing memory traces (Abrari et al 2008;Cai et al 2006;Debiec and Ledoux 2004;Maroun and Akirav 2007;Przybyslawski et al 1999;Tronel and Alberini 2007;Yang et al 2005). Processes that are thought to be influenced by these drugs are postretrieval mechanisms like extinction and reconsolidation (Suzuki et al 2004).…”
mentioning
confidence: 99%
“…Tronel and Alberini (2007) have recently shown that reconsolidation might also be dependent on the glucocorticoid system, as they found that a glucocorticoid receptor antagonist can disrupt conditioned fear in rats after reactivation of an inhibitory avoidance memory. In line with that, Maroun and Akirav (2007) have found an impairing effect of stress on reconsolidation in rats, which was reversed by a glucocorticoid receptor antagonist. However, cortisol may also impair memory after reactivation by enhancing extinction rather than reducing reconsolidation (Abrari, RashidyPour, Semnanian, & Fathollahi, 2008;Cai, Blundell, Han, Greene, & Powell, 2006).…”
Section: Introductionsupporting
confidence: 76%
“…In a previously reported study, we examined the effects of elevated stress hormones on post-retrieval processes in humans (Tollenaar, Elzinga, Spinhoven, & Everaerd, 2008b). In line with animal studies (Maroun & Akirav, 2007), a post-retrieval decline in memory performance was observed when memories were reactivated during stress (5 weeks after encoding). However, whether cortisol or other stress hormones were active in this process remains unclear.…”
Section: Introductionmentioning
confidence: 85%
“…To persist, this labile memory must be reconsolidated. The process of postreactivation memory destabilization and reconsolidation has been demonstrated in numerous species and for myriad memory types (Misanin et al, 1968;Sara, 2000;Nader, 2003;Hardt et al, 2010;Alberini, 2011), including object recognition memory (Bozon et al, 2003;Kelly et al, 2003;Akirav and Maroun, 2006;Rossato et al, 2007;Maroun and Akirav, 2008;Lima et al, 2009;Winters et al, 2009;Davis et al, 2010;Romero-Granados et al, 2010).…”
Section: Introductionmentioning
confidence: 99%